Evaluation of an engineered vascular graft exhibiting somatic growth in lambs to model repair of absent pulmonary artery branch - Zeeshan H. Syedain; Matthew Lahti; Gurumurthy Hiremath; James Berry; John P. Carney; Jill Schappa Faustich; Tate Shannon; Andrea Rivera; Hadi Wiputra; Zhitian Shi; Richard Bianco; Robroy MacIver; et al. (Communications Medicine)
Abstract Background Growth is the holy grail of tissue implants in pediatrics. No vascular graft currently in use for surgical repairs of congenital heart defects has somatic growth capacity. Methods Biologically-engineered grafts (6 mm) grown from donor ovine fibroblasts in a sacrificial fibrin gel were implanted into the left pulmonary branch of 3-month old lambs for 3, 6, and 18 months. A control group of Propaten® PTFE grafts was implanted for 6 months. Results The engineered grafts exhibit extensive site-appropriate recellularization after only 3 months and near-normal increase of diameter from the preimplant value of 6 mm to 12.9 mm and also a doubling of length from 6.0 mm to 13.0 mm at 6 months (n = 3) associated with apparent somatic graft growth (collagen content increase of 265% over 18-month, n = 2), along with excellent hemodynamics and no calcification, in contrast to the Propaten® grafts. The left-right flow distribution is nearly 50–50 for the engineered grafts at 6 months (n = 3) compared to about 20–80 for the Propaten® grafts (n = 3), which have less than one-half the diameter, a 6-fold higher pressure gradient, and stunted vascular development downstream of the graft. The engineered grafts exhibit a stable diameter over months 12–18 when the lambs become adult sheep (n = 2). Conclusions This study supports the use of these regenerative grafts with somatic growth capacity for clinical trial in patients born with a unilateral absent pulmonary artery branch, and it shows their potential for improving development of the downstream pulmonary vasculature.